2003
DOI: 10.1016/j.toxlet.2003.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mouse liver respiration by Chelidonium majus isoquinoline alkaloids

Abstract: 15The alkaloids from Chelidonium majus L. which had a significant inhibitory effect in mitochondrial respiration were those which contain a positive charge due to a quaternary nitrogen atom, i.e., chelerythrine, sanguinarine, berberine and coptisine, both with malate + glutamate or with succinate as substrates. When malate + glutamate was used as substrate, chelerythrine and berberine, which contain methoxy groups, were particularly more active, since they had a strong effect even at low concentrations. In sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 18 publications
4
28
0
1
Order By: Relevance
“…These data suggest that berberine is able to reduce oxygen-dependent glucose oxidation in mitochondria. This observation is consistent with berberine activity in the purified mitochondria, in which berberine inhibited NADlinked respiration (1,11,12). The reduction in oxygen consumption was associated with an increase in glycolysis, suggesting that berberine stimulates ATP production through glycolysis.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These data suggest that berberine is able to reduce oxygen-dependent glucose oxidation in mitochondria. This observation is consistent with berberine activity in the purified mitochondria, in which berberine inhibited NADlinked respiration (1,11,12). The reduction in oxygen consumption was associated with an increase in glycolysis, suggesting that berberine stimulates ATP production through glycolysis.…”
Section: Discussionsupporting
confidence: 86%
“…Although AMPK is activated by berberine, the metabolic conditions that lead to this effect require further investigation. Berberine was shown to inhibit the citric acid cycle in isolated mitochondria (1,11,12). However, it is not clear whether this activity can be observed in living cells for AMPK activation.…”
mentioning
confidence: 99%
“…Previous studies in fact have shown that berberine inhibits NADH dehydrogenase and respiratory activity [23,37]. In addition, mitochondrial participation in berberine-induced apoptosis has been demonstrated in a number of studies [2,6,11,38].…”
Section: Discussionmentioning
confidence: 90%
“…It was shown that sanguinarine induced a programmed the other type of cell death in the erythroleukemia K562 cell line by causing a significant increase in the expression of proapoptotic Bax protein and activation of caspase cascade [1,29]. Some alkaloids were found to block the respiration processes in mitochondria [2]. We have demonstrated (in a submitted article), that the intercalating properties of specific celandine alkaloids correlated with their ability to induce dissipation of trans-membrane potential and caused alteration in the permeability of the inner mitochondrial membrane; in turn, this may have led to a release of the pro-apoptotic proteins from mitochondria to cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Chelidonine was shown to interact with tubulin in target cells and cause their mitotic arrest [18]. The molecules of chelerythrine, sanguinarine, berberine and coptisine possess a positive charge due to the presence of quaternary nitrogen, and exhibit a significant inhibitory effect on the mitochondrial respiration [2]. Sanguinarine and chelerythrine contain reactive imine groups and are capable of inhibiting the activity of enzymes and other proteins which possess the nucleophilic groups [8].…”
Section: Introductionmentioning
confidence: 99%